2015
DOI: 10.1016/j.ccell.2015.03.006
|View full text |Cite|
|
Sign up to set email alerts
|

Convergent Mutations and Kinase Fusions Lead to Oncogenic STAT3 Activation in Anaplastic Large Cell Lymphoma

Abstract: Summary A systematic characterization of the genetic alterations driving ALCLs has not been performed. By integrating massive sequencing strategies, we provide a comprehensive characterization of driver genetic alterations (somatic point mutations, copy number alterations, and gene fusions) in ALK− ALCLs. We identified activating mutations of JAK1 and/or STAT3 genes in ∼20% of 155 ALK− ALCLs and demonstrated that 38% of systemic ALK− ALCLs displayed double lesions. Recurrent chimeras combining a transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
262
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 388 publications
(277 citation statements)
references
References 35 publications
13
262
2
Order By: Relevance
“…Mutations were found in up to 70% of T-LGL and 30-40% of NK-LGL leukemia patients [50,[77][78][79]. Mutations of STAT3 were also identified in 5% of cutaneous forms of ALCL (cALCL) and 10% of ALK-negative ALCL [52]. Interestingly, in 7% of ALK-negative ALCL mutations of STAT3 and JAK1 occurred concomitantly.…”
Section: Constitutive Active Jak/stat Pathway In Other Tumorsmentioning
confidence: 90%
See 2 more Smart Citations
“…Mutations were found in up to 70% of T-LGL and 30-40% of NK-LGL leukemia patients [50,[77][78][79]. Mutations of STAT3 were also identified in 5% of cutaneous forms of ALCL (cALCL) and 10% of ALK-negative ALCL [52]. Interestingly, in 7% of ALK-negative ALCL mutations of STAT3 and JAK1 occurred concomitantly.…”
Section: Constitutive Active Jak/stat Pathway In Other Tumorsmentioning
confidence: 90%
“…Interestingly, in 7% of ALK-negative ALCL mutations of STAT3 and JAK1 occurred concomitantly. Functional tests of JAK1 and STAT3 mutants showed that individual aberrations could cooperate when co-expressed [52]. The mutations detected in leukemia and lymphoma patients are located in exons 20 and 21 in the SH2 domain of STAT3.…”
Section: Constitutive Active Jak/stat Pathway In Other Tumorsmentioning
confidence: 98%
See 1 more Smart Citation
“…Reports on patient mutation sequencing analyses of various T-cell lymphoma subtypes frequently include the JAK/STAT pathway, where JAK1, JAK3, STAT3 , and STAT5B are predominantly mutated to cause hyperactivation [64,70,7578]. Importantly, ALK − ALCL is associated with STAT3 activation [64] and recurrent, somatic activating mutations in the closely related STAT5B gene were reported.…”
Section: Targets In Ptcl and Driver Mutationsmentioning
confidence: 99%
“…Importantly, ALK − ALCL is associated with STAT3 activation [64] and recurrent, somatic activating mutations in the closely related STAT5B gene were reported. The STAT5B N642H mutation occurs with the highest frequency in PTCL, whereby most mutations cluster in the SH 2 and C-terminal transactivation domain [70,75,7882].…”
Section: Targets In Ptcl and Driver Mutationsmentioning
confidence: 99%